In vivo Protein Evolution, Next Generation Protein Engineering Strategy: from Random Approach to Target-specific Approach - Kim, Jin Young; Yoo, Hee-Wang; Lee, Pyung-Gang; Lee, Sun-Gu; Seo, Joo-Hyun; Kim, Byung-Gee (Biotechnology and bioprocess engineering, 2019)
In vivo protein evolution is a protein engineering approach that is performed by both generating mutagenesis libraries and selecting desired mutants in a cell. Despite its clear advantages in some aspects, the approach has not much been popularized compared to in vitro protein evolution methods which employ in vitro mutagenesis. The reason behind this unpopularity is the limitations in the low library diversity and specificity of in vivo mutagenic methods compared to those of in vitro mutagenic methods. While various non-specific and specific in vitro mutagenic methods, which allowed us to use computational design principles as well as random approach in the design of mutant library, had been developed, in vivo mutagenic methods were stalled at the step of random mutagenesis since the in vivo generation of target-specific library with high specificity and broad mutational spectra is quite challenging. Recently, various in vivo protein mutagenesis methods have been developed to generate rather focused libraries in a target-specific manner, thanks to the significant decrease in the price of oligomer synthesis and better understanding of DNA targeting systems. In this review, we examined the trends of in vivo protein evolution and inspect some of the state-of-the-art techniques that were recently introduced for in vivo protein mutagenesis in a target-specific manner. In vivo protein mutagenesis is a subject undergoing intense study and will become more specific and thorough simultaneously.